OUR DATA BODIES. RE-FRAMING OUR CONCEPTUAL AND NORMATIVE RELATIONSHIP WITH PERSONAL DATA - Suárez-Gonzalo, Sara; López-Gabrielidis, Alejandra (AoIR Selected Papers of Internet Research, 2023)
The rapid development of data-driven technologies has led to manifold concerns on how to protect citizens from the effects of massive data exploitation, especially when “personal data” are at stake, since they are the object of a fundamental right. Personal data are legally defined as any information “relating to” an identified or identifiable natural person, the right holder. However, it is unclear in which particular sense personal data relate to a person: which is the specific type of direct connection between them. In our view, this is a crucial question both from a conceptual and a normative point of view that the academic literature has not yet addressed in enough depth. In light of this, our paper aims at advancing knowledge towards a more accurate conception of our relationship with personal data. To do so, we firstly discuss the main recent conceptions on the issue: data as property, data as raw material and data as labour. Secondly, we argue why none of them seems to be accurate from a conceptual point of view or desirable from a socio-political perspective. Finally, we propose to understand personal data as _part of oneself_ and our relationship with them as the one we have with our bodies or their parts, with _our data bodies_. We end up discussing the implications of the proposed conception, both from a conceptual and from a normative perspective.